A biocompatibility study of new nanofibrous scaffolds for nervous system regeneration. Issue 1 (26th November 2015) - Raspa, A.; Marchini, A.; Pugliese, R.; Mauri, M.; Maleki, M.; Vasita, R.; Gelain, F.
Abstract : Blend, coaxial I, coaxial II and annealed microchannels were fabricated with an electrospinning setup and the fiber morphologies were characterized with a scanning electron microscope (SEM). Microtubes were implanted into rodent spinal cord to analyze biocompatibility. Abstract : The development of therapeutic approaches for spinal cord injury (SCI) is still a challenging goal to achieve. The pathophysiological features of chronic SCI are glial scar and cavity formation: an effective therapy will require contribution of different disciplines such as materials science, cell biology, drug delivery and nanotechnology. One of the biggest challenges in SCI regeneration is to create an artificial scaffold that could mimic the extracellular matrix (ECM) and support nervous system regeneration. Electrospun constructs and hydrogels based on self-assembling peptides (SAPs) have been recently preferred. In this work SAPs and polymers were assembled by using a coaxial electrospinning setup. We tested the biocompatibility of two types of coaxially electrospun microchannels: the first one made by a core of poly(ε-caprolactone) and poly(d, l -lactide- co -glycolide) (PCL–PLGA) and a shell of an emulsion of PCL–PLGA and a functionalized self-assembling peptide Ac-FAQ and the second one made by a core of Ac-FAQ and a shell of PCL–PLGA. Moreover, we tested an annealed scaffold by PCL–PLGA microchannel heat-treatment. The properties of coaxial scaffolds were analyzed using scanning electron microscopy (SEM), Fourier transform spectroscopy (FTIR), contact angle measurements and differential scanning calorimetry (DSC). In vitro cytotoxicity was assessed via viability and differentiation assays with neural stem cells (NSCs); whereas in vivo inflammatory response was evaluated following scaffold implantation in rodent spinal cords. Emulsification of the outer shell turned out to be the best choice in terms of cell viability and tissue response: thus suggesting the potential of using functionalized SAPs in coaxial electrospinning for applications in regenerative medicine.